Raul Seixas: a mosca na sopa da ditadura militar - censura, tortura e exílio (1973-1974) - Santos, Paulo dos (2007)
This dissertation aims to rescue the importance of the singer and composer Raul Seixas (1945-1989) in the period between the military dictatorship and the promulgation of 1988 Constitution. It seeks, still, to verify his insertion into the Brazilian artistic scenario and in other segments during the 1970 decade, as the counterculture, the censorship, the repression and the torture of all considered subversive. Recognized as composer of many talents, the singer figures among the most renowned artists of the last years in the Brazilian popular music. Discloser of Alternative Society, that in full military regime had as slogan "do what you want, because it is everything within the law", he did of his music speeches having an innovative spirit to say old things with new characteristics, mixing differentiated rhythms that, according to the artist, "had the same malices", such as rock and roll and the baião (Brazilian folk music and dance), and, thus, constituting trends. This study is divided in three chapters: in the first - "If today I am a star, tomorrow it has already faded... of Raulzito to Raul Seixas" - they narrate the artist's path since the beginning of his career, the success and the last years of life. In the second "The monster SIST is gargantuan and crazy to have sex with me... Raul Seixas and the Censorship" - the censorship, the manifest comic book, main theoretical instrument for the implementing the Alternative Society in Brazil, and the dialogue between the censorship and the censured music, are studied. Finally, in the third party "Because there are just truths to say, to declare... Raul Seixas and the Federal Police" it presents how the persecution, the artist s prison, torture and exile took place